EPISTEMOLOGY OF ISLAMIC EDUCATION - Zailani Zailani (Proceeding International Seminar of Islamic Studies, 2021)
This article entitled Epistemology of Islamic Education aims to explain the purpose and way of obtaining knowledge from a philosophical point of view. The methods used in this paper are qualitative research, type of literature research, library research. The data used are documents, such as books, manuscripts, magazines, and other archive data that can support this writing. The findings and discussions found that the number of reviews from Islamic education figures related to Islamic education is reviewed from a philosophical perspective. But in general Islamic education is related to the concept of thinking that is based on the Qur'an and As-sunnah. These two sources became the main avenues in the whole formation of man, both physical and spiritual. While the purpose of Islamic education to direct people to their nature, as Insanul Kamil and Islam provide several paths in gaining knowledge, Through the five senses, experiences, and intuition.